Qualitative study of socio-economic and family factors in the stigmatization process in dementia in sub-Saharan Africa - (:unkn) unknown (My University, 2017)
The aging population is becoming a major political issue. It results in an increase in the prevalence of non-communicable diseases including dementia. Dementia is a major public health problem worldwide and in sub-Saharan Africa. It is assimilated to a real "Alzheimer tsunami", because of the growing number of people with dementia. In 50% of cases, they are taken care of in residential care facilities for dependent elderly people or by ambulatory professionals in high-income countries. By cons, in low and middle incomes countries, their taken care is informal, provided by informal caregivers who are neither trained nor encouraged, having links of kinship as filiation, alliance and germanic with people with dementia. In sub- Saharan Africa, mental illnesses are rich in pejorative and demeaning sociocultural representations. The main objective was to describe socio-economic and family factors in the process of stigmatization of people with dementia in urban and rural areas in the Republic of Congo. An ethnological study was conducted in three months’ immersion on the ground. Non-directive interviews conducted in the local (Lingala, Kituba, Mbochi, Teke and Lari) and official languages (French) and complemented by participant observation were used to collect all the data. They were literally transcribed before their classification into themes. Informal caregivers were mainly daughters-in-law and granddaughters. The latter were considered as purveyors of informal care to an estimated duration between 10 to 15 hours a day, against daughters-in-law considered abusers and available between 2 to 6 hours per day. The irregular income of informal caregivers associated with the socio-cultural representations of people with dementia first led to their care by the syncretic churches, with strict diets for exorcism sessions. The second resort was traditional healers using medicinal plants, prayers-incantations and scarifications. Some people with dementia were acc
Keywords: African Research